The wish - fulfilling jewel : the practice of guru yoga according to the Longchen Nyingthig tradition - Khyentse, Dilgo; Tenzin, Konchog (Delhi : Katmandu : Shechen & Shambhala, 2004)
In the Tibetan Buddhist tradition, devotion to one's guru or spiritual master is considered to be of the utmost importance in spiritual practice. The instructions of Dilgo Khyentse Rinpoche, based upon the teachings of the great eighteenth-century saint and visionary Rigdzin Jigme Lingpa, focus on the devotional practices of Guru Yoga, "Merging with the Mind of the Guru."
Includes notes.
Keywords: Guru worship (Rite) -- Buddhism; Buddhism -- China -- Tibet Autonomous Region; Rnying-ma-pa (Sect) -- Doctrines